Consistency between the ichthyotoxicity and allelopathy among strains and ribotypes of Margalefidinium polykrikoides suggests that its toxins are allelochemicals - Yang, Huijiao; Gobler, Christopher J.; Tang, Ying Zhong (Frontiers in Marine Science, 2022)
Harmful algal blooms (HABs) of the ichthytoxic dinoflagellate Margalefidinium polykrikoides have caused mass mortality of marine life around the world. While its toxic effects can impact fish, bivalves, coral, zooplankton, and even other phytoplankton, the toxin(s) and allelochemical(s) eliciting these impacts have yet to be definitely identified, leaving open the question as to whether its toxicity and allelopathic effects are caused by the same chemical agents. In this study, we investigated the ability of 10 strains of M. polykrikoides with different geographic origins and ribotypes to cause mortality in two strains of the dinoflagellate, Akashiwo sanguinea (allelopathy), and the sheepshead minnow, Cyprinodon variegatus (toxicity). Results showed that the potency of allelopathy against both strains of A. sanguinea and toxicity to the fish were significantly correlated across strains of M. polykrikoides (p < 0.001 for all). These results strongly support the notion that the major allelochemicals and toxins of M. polykrikoides are identical chemicals, an ecological strategy that may be more energetically efficient than the separate synthesis of toxins and allelochemicals as has been reported in other HABs. Our results also highlight the vital significance of the definitive identification of allelochemicals and toxins of M. polykrikoides and of the quantitative characterization of these compounds in the field where HABs of M. polykrikoides occur during blooms.